Indonesian English Teachers’ Perceptions on Using Online Teaching Platforms - Nur, Johari; Gushendra, Rizky (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Due to Covid-19 Pandemic, all teachers in Indonesia are required to teach students remotely using appropriate online teaching platforms. There various teaching platforms to be utilized such as Whatsapp, Edmodo, Google Classroom, Ruang-Guru, Kahoot, Google Meet, Zoom Cloud, etc. These platforms enable the teachers to simply interacting with the students in teaching-learning processes. The objective of this research is to explore the Indonesian English teacher’ perceptions on using online teaching platforms. This research uses a quantitative approach. The subject of this research is 40 English teachers of Senior High Schools in Kampar, Riau. Questionnaires are used as a technique of collecting data. Results prove that most of the English teachers have positive perceptions on the usefulness, ease of use, and accessibility aspects of online teaching platforms.